2016
DOI: 10.1111/ejn.13408
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal shape alterations are associated with regional Aβ load in cognitively normal elderly individuals

Abstract: Aβ deposition is a driving force of Alzheimer's disease pathology and can be detected early by amyloid positron emission tomography. Identifying presymptomatic structural brain changes associated with Aβ deposition might lead to a better understanding of its consequences and provide early diagnostic information. In this respect we analyzed measures of cortical thickness and subcortical volumes along with hippocampal, thalamic and striatal shape and surface area by applying novel analysis strategies for structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 63 publications
(73 reference statements)
3
12
0
Order By: Relevance
“…However, evaluation of the hippocampus performed to date has been restricted to whole volume measurement only. M. Chakravarty et al, 2015;McDermott et al, 2019;Schroeder et al, 2017). M. Chakravarty et al, 2015;McDermott et al, 2019;Schroeder et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, evaluation of the hippocampus performed to date has been restricted to whole volume measurement only. M. Chakravarty et al, 2015;McDermott et al, 2019;Schroeder et al, 2017). M. Chakravarty et al, 2015;McDermott et al, 2019;Schroeder et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This concurs with the occurrence of significant amounts of Aβ in the thalamus of AD (Braak & Braak, ). Shape abnormalities in the thalamus associated with Aβ have also been reported in cognitively normal individuals (Schroeder et al, ) as well as in MCI patients who showed cognitive worsening over a 2‐year period (Kalin et al, ). Interestingly, we also found that some of the surface change in the thalamus were also due to changes in shape only (i.e., surface remains abnormal even when analyses were corrected for size and global scalings), particularly in regions which did not show surface changes when investigating the effect of local volume change.…”
Section: Discussionmentioning
confidence: 83%
“…A vertex‐based surface approach was used to investigate Aβ‐associated local surface changes in subcortical structures and whether these changes related more to local volume or shape. Surface‐based approaches have proven efficient in the detection of subtle surface abnormalities in subcortical structures in AD, MCI, and cognitively normal individuals (Csernansky et al, ; de Flores et al, ; Kalin et al, ; Leh et al, ; Schroeder et al, ). Unlike our previous analyses using subcortical overall volumes, we found that subcortical regional PiB retention values were associated with the surface of the bilateral hippocampus and thalamus and the right pallidum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations